Cinema's alchemist : the films of Péter Forgács (Visible evidence, 2011)
Introduction / Bill Nichols -- Setting the Scene. Péter Forgács: an interview / Scott MacDonald -- The memory of loss: Péter Forgács' Saga of family life and social hell / Péter Forgacs and Bill Nichols, in dialogue -- The Holocaust Films. Toward a new historiography: the aesthetics of temporality / Ernst van Alphen -- Ordinary film: The maelstrom / Michael S. Roth -- Historical discourses of the unimaginable: The maelstrom / Michael Renov -- Waiting, hoping, among the Ruins of All the Rest / Kaja Silverman -- The trace: framing the presence of the past in Free fall / Malin Wahlberg -- Other films/other contexts. How to make history perceptible: The Bartos family and the private Hungary series / Roger Odin -- Found images as witness to Central European history: a Bibø reader and Miss Universe 1929 / Catherine Portuges -- Reenvisioning the documentary fact: on saying and showing in Wittgenstein Tractatus and bourgeois dictionaries / Tyrus Miller -- The world rewound: Wittgenstein Tractatus / Whitney Davis -- Taking the part for the whole: some thoughts inspired by the film music of Tibor Szemzø / Tamøs Korønyi -- Analytical spaces: the installations of Péter Forgács / Laszlo F. Føldønyi -- Reorchestrating history: transforming The Danube exodus into a database documentary / Marsha Kinder